(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2021)
In Malaysia, disputes concerning custody rights are among the frequently-debated topics in cases of conversion to Islam, if it involves a marriage previously registered under civil law. Since coming into force, a frequent issue that has arisen is the rights of convert spouses under the Law Reform (Marriage and Divorce) Act 1976 (Act 164), specifically Sections 3 and 51, as the muallaf (convert to Islam) does not have the right to petition for dissolution of marriage under this Act. However, in 2017, amendments were made to this Act to bring about better and more efficient resolutions to any legal issues arising in such matters. Therefore, this article aims to compare the concept of hadhanah (care and protection of children) in Islamic law with custody rights under Malaysian civil law. The factors that frequently give rise to conflict were analysed, as well as the implications of the 2017 amendments (Act 164) concerning the application procedure for custody rights of convert spouses. Library research was employed to collect data for content analysis. The findings show that the amendments are able to aid in resolving issues concerning divorces of converts who were previously bound to a civil marriage without the right to petition for dissolution. The amendment also allows both spouses the right to apply for custody of a child after their divorce has been finalized by the civil court. The study further recommends that in such cases, child welfare, and not the rights of the converted parent, should be the main concern at all times. Keywords: Child custody, Muallaf, Islamic law, civil law